A new species of the genus Spiritiops Lugo-Ortiz & McCafferty (Ephemeroptera, Baetidae) from the Pantepui biogeographical province - Nieto Peñalver, María Carolina (2012)
The genus Spiritiops was described by Lugo-Ortiz & McCafferty in 1998. Since then, only the type species, S. silvudus, was reported from different countries, such as Brazil, French Guiana, Surinam and Venezuela. In the last years, various international speleological expedition explored summits of some table mountains called tepuis in Guyana region in south-eastern Venezuela. Here we describe a new species of the genus Spiritiops, found at three tepuis (Auyán-tepui, Churí-tepui and Mt. Roraima) during above mentioned speleological expeditions.